The Development of College English Teachers' Pedagogical Content Knowledge in Moral Education Integrated College English Teaching in China. - Lina Wang; Samad, Arshad Abd; Madhubala Abdullah, Nur Surayyah (Pertanika Journal of Social Sciences & Humanities, 2024)
In mainland China, college English (CE) teachers have been actively involved in integrating moral education into college English courses to promote a more rounded development of students. In the transition from traditional college English teaching to moral education integrated college English (MECE) teaching, college English teachers' pedagogical content knowledge (PCK) is subject to change. This study was designed as a qualitative case study to conduct a 3-year investigation to investigate the changes in PCK among college English teachers through the transition from CE to MECE. The trajectory of PCK development was collected from three teachers via content representation (CoRe), semi-structured interviews, and teaching materials. As suggested from the findings, in the process of transition from CE to MECE, the pathways that led to changes in PCK are specific objective-based study with reflection, participating in training sessions and workshops, interacting in effective online/face-to-face communities, as well as embracing the new relationship of co-learning with students. The findings underscored the need for comprehensive professional development programs that equip college English teachers with the skills to integrate moral education into their instruction. The research highlights the practical challenges that must be overcome by teacher training programs in being proactive, responsive, and adaptive to an evolving educational landscape, ensuring teachers are equipped not just to meet new pedagogical demands but also to actively engage in the complex discourse on integrating moral education.